2008
DOI: 10.1007/s00127-008-0420-3
|View full text |Cite
|
Sign up to set email alerts
|

Mexican American caregivers’ coping efficacy

Abstract: Caregivers' coping efficacy has heuristic value for research on the alleviation of caregiver psychological distress and the promotion of family caregiver behaviors associated with a benign course of illness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 68 publications
1
8
0
Order By: Relevance
“…The findings revealed that the family caregivers of relatives with schizophrenia underwent major psychological distress. This was consistent with the findings of similar studies that confirmed that family caregivers experienced substantial stress and burden related to care giving (Awad & Voruganti 2008, GJI et al 2009, Yusuf et al 2009, Mizuno et al 2013). The literature suggests that a chronic illness of a family member can result in strain for the caregiver due to the difficult tasks of constantly caring for another person (Brady & McCain 2004, Ganguly et al 2010.…”
Section: Discussionsupporting
confidence: 91%
“…The findings revealed that the family caregivers of relatives with schizophrenia underwent major psychological distress. This was consistent with the findings of similar studies that confirmed that family caregivers experienced substantial stress and burden related to care giving (Awad & Voruganti 2008, GJI et al 2009, Yusuf et al 2009, Mizuno et al 2013). The literature suggests that a chronic illness of a family member can result in strain for the caregiver due to the difficult tasks of constantly caring for another person (Brady & McCain 2004, Ganguly et al 2010.…”
Section: Discussionsupporting
confidence: 91%
“…A multicultural study of family caregiving found that 75% of Latinos and 60% of African Americans lived with their families, compared to 30% of European American patients with severe mental illness (Guarnaccia, ). Studies have consistently found that a majority of Latinos of Mexican origin with schizophrenia live with family members in the community (Barrio, Yamada, Hough, et al., ; Jenkins & Schumacher, ; Kopelowicz, Zarate, Gonzalez Smith, Mintz, & Liberman, ; Magaña, Ramírez García, Hernández, & Cortez, ; Ramírez García, Hernández, & Dorian, ). These findings exemplify the caregiving ideology within ethnic cultures that reflects adaptive attributions and expectations regarding the loved one's illness (Guarnaccia, ; Pickett, Cook, & Heller, ).…”
mentioning
confidence: 57%
“…Thus, family involvement in medication use may be a protective factor for adherence (Lanouette et al, 2009). Further, these findings point to the importance of families regarding adherence and may be particularly relevant for Latinos with serious mental illness, who are more likely to live with their family than other groups (Barrio et al, 2003; Ramírez García et al, 2009). …”
mentioning
confidence: 87%